Encyclopedia of heart diseases - Khan, M. I. Gabriel (Elsevier/Academic Press, 2006)
The Encyclopedia of Heart Diseases is an accurate and reliable source of in-depth information on the diseases that kill more than 12 million individuals worldwide each year. In fact, cardiovascular diseases are more prevalent than the combined incidence of all forms of cancer, diabetes, asthma and leukemia. In one volume, this Encylopedia thoroughly covers these ailments and also includes in-depth analysis of less common and rare heart conditions to round out the volume's scope. Researchers, clinicians, and students alike will all find this resource an invaluable tool for quick reference befor.